Gambaran Ketrampilan Pemeriksaan Payudara Sendiri Pada Ibu - Ibu Pembinaan Kesejahteraan Keluarga Di Rw V Desa Karanggeneng Boyolali - Nurhidayati, Hanik; , Sulastri, S.Kp., M.Kes (2017)
Cancer is one of the leading causes of death worldwide, one of which is breast cancer. The number of cases of breast cancer in 2013 in Indonesia is 61,682 cases. Given the early detection and treatment of early-stage cancer is better than the advanced stage, then the early diagnosis is very necessary women by the way BSE. Preliminary study results have been done health education about breast self-examination in the mother of PKK. The purpose of this study was to determine the description of breast self-examination skills in mothers Development of Family Welfare. The research type is quantitative, descriptive research design, cross sectional approach. The population in this study were all mothers of PKK members in RW V Karanggeneng Boyolali Village as many as 318 respondents. Determination of sample data using slovin formula and sampling accidental sampling technique, the number of sample 76 respondents. Meter with checklist about BSE. Analysis of data with univariate. The results of this study are the characteristics of mothers based on the age of the average age of the mother of 32.68 years, including in the productive age. Most of the maternal education is basic (elementary and junior high). The work of the respondents partially does not work. Breast self-examination skills in mothers Family Welfare Development has an average of 46.05 or in the less skilled category. The results of the research into information for health personnel in providing care nursing maternity in the community about early detection of breast cancer in particular and is expected to always active in various community activities and provide counseling counseling so as to improve public knowledge about breast cancer breast cancer early detection by way of BSE